2016
DOI: 10.1038/srep36412
|View full text |Cite
|
Sign up to set email alerts
|

A novel enzyme with antioxidant capacity produced by the ubiquitous skin colonizer Propionibacterium acnes

Abstract: The role of the skin microbiota in human health is poorly understood. Here, we identified and characterized a novel antioxidant enzyme produced by the skin microbiota, designated RoxP for radical oxygenase of Propionibacterium acnes. RoxP is uniquely produced by the predominant skin bacterium P. acnes, with no homologs in other bacteria; it is highly expressed and strongly secreted into culture supernatants. We show that RoxP binds heme, reduces free radicals, and can protect molecules from oxidation. Striking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
76
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(77 citation statements)
references
References 49 publications
1
76
0
Order By: Relevance
“…Our findings support the view that a simple classification of pathogenicity based on the phylotype level, while convenient, is not adequate for the complex relationship between the bacteria and the host. In fact, recent studies found positive traits of C. acnes on the host supporting a potential symbiotic relationship (24,25). These findings highlight that further research is necessary to fully understand the positive and negative role of C. acnes in skin homeostasis.…”
Section: Discussionmentioning
confidence: 84%
“…Our findings support the view that a simple classification of pathogenicity based on the phylotype level, while convenient, is not adequate for the complex relationship between the bacteria and the host. In fact, recent studies found positive traits of C. acnes on the host supporting a potential symbiotic relationship (24,25). These findings highlight that further research is necessary to fully understand the positive and negative role of C. acnes in skin homeostasis.…”
Section: Discussionmentioning
confidence: 84%
“…On one hand, P . acnes is known to produce propionate, a short chain fatty acid which can promote regulatory T cell in the colon [ 52 ], as well as RoxP (radical oxygenase of Propionibacterium acnes ), which can potentially reduce oxidative stress and prevent skin inflammation [ 53 ]. In contrast, certain strains of P .…”
Section: Discussionmentioning
confidence: 99%
“…Total RNA from P. acnes (KPA171202 (type IB), and 12.1.L1 (type IA)) grown under anaerobic conditions to the exponential and stationary growth phase in BHI medium at 37 °C was prepared as described previously [ 43 ]. The cDNA libraries were constructed by Vertis Biotechnology AG, Freising, Germany, as previously described [ 44 , 45 ].…”
Section: Methodsmentioning
confidence: 99%